Mechanical behavior of polymers PBXW-128 and PBXN-110 under uniaxial and multiaxial compression at different strain rates and temperatures - Çolak, ÖÜ (AMER SOC TESTING MATERIALS, 2004)
The influence of strain rate, temperature, and confining pressure on the mechanical behavior of PBXN-110 binder inert (hydroxy-terminated polybutadiene (HTPB)) and PBXW-128 simulant inert, which is mixed with small particles of sugar, approximately 50% by weight, is presented in this paper. The polymer PBXN-110 is used as the matrix for the particle-reinforced polymer composite (PBXW-128); the latter is the mock or inert equivalent of actual explosive material. Stress-strain response of both polymeric materials under uniaxial compression is found to be dependent on the strain rate. On one hand, it is observed that PBXW-128 exhibits temperature-dependent behavior, while the mechanical response of PBXN-110 is not significantly affected at temperatures above the glass transition temperature. Compression experiments in the presence of confining pressure reveal that the stress-strain response of each material is rate insensitive.
Keywords: polymeric materials; rate dependency; temperature effect; compression; confining pressure; hydroxyl-terminated polybutadiene; MODEL; Materials Science